Environmental and Aerosolized Severe Acute Respiratory Syndrome Coronavirus 2 Among Hospitalized Coronavirus Disease 2019 Patients. (9th September 2020) - Binder, Raquel A; Alarja, Natalie A; Robie, Emily R; Kochek, Kara E; Xiu, Leshan; Rocha-Melogno, Lucas; Abdelgadir, Anfal; Goli, Sumana V; Farrell, Amanda S; Coleman, Kristen K; Turner, Abigail L; Lautredou, Cassandra C; et al.
Abstract: During April and May 2020, we studied 20 patients hospitalized with coronavirus disease 2019 (COVID-19), their hospital rooms (fomites and aerosols), and their close contacts for molecular and culture evidence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Among >400 samples, we found molecular evidence of virus in most sample types, especially the nasopharyngeal (NP), saliva, and fecal samples, but the prevalence of molecular positivity among fomites and aerosols was low. The agreement between NP swab and saliva positivity was high (89.5%; κ = 0.79). Two NP swabs collected from patients on days 1 and 7 post–symptom onset had evidence of infectious virus (2 passages over 14 days in Vero E6 cells). In summary, the low molecular prevalence and lack of viable SARS-CoV-2 virus in fomites and air samples implied low nosocomial risk of SARS-CoV-2 transmission through inanimate objects or aerosols. Abstract : In studying 20 hospitalized COVID-19 patients, we found the highest prevalence of severe acute respiratory syndrome coronavirus 2 RNA among patients' nasopharyngeal and saliva samples (high correlation), but also RNA on fomites and in room air. However, only 2 nasopharyngeal swabs were culture positive.